1998
DOI: 10.1016/s0014-5793(98)00857-6
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of mitochondrial DNA and RNA level in human fibroblasts with impaired vitamin B12 coenzyme synthesis

Abstract: Alterations of mitochondrial (mt) nucleic acid metabolism in methylmalonic aciduria (MMA) were studied in two cell lines from skin fibroblasts of patients with mitochondrial (GM00595) or cytosolic (GM10011) defects in the biosynthesis pathways of cobalamin coenzymes. The mtDNA level increased two-fold in GM00595 cells, which carry a mt defect in the adenosylcobalamin synthesis, whereas no appreciable change was found in GM10011 cells. The content of the two rRNAs 16S and 12S mtRNAs, normalized for the mtDNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Only the ND6 gene is transcribed independently (for review, see Taanman 1999). Under specific inhibitory or pathological conditions, the levels of only a few of the mitochondrial transcripts changed (Collombet et al 1997;Cantatore et al 1998;Heddi et al 1999). This indicated that modification of the steady-state level of mitochondrial transcripts was not always a simultaneously and proportionate event affecting all the 13 OXPHOS transcripts.…”
Section: 4mentioning
confidence: 99%
“…Only the ND6 gene is transcribed independently (for review, see Taanman 1999). Under specific inhibitory or pathological conditions, the levels of only a few of the mitochondrial transcripts changed (Collombet et al 1997;Cantatore et al 1998;Heddi et al 1999). This indicated that modification of the steady-state level of mitochondrial transcripts was not always a simultaneously and proportionate event affecting all the 13 OXPHOS transcripts.…”
Section: 4mentioning
confidence: 99%
“…Change of levels of mtDNA production may increase the generation of mitochondrial ROS. Corticotropin, which induces the secretion of other hormones, including corticosterone, and vitamin 12 are involved in regulating mtDNA and mtRNA expression4344. Gadaleta et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that mtDNA genotype may influence nuclear gene expression, as demonstrated in yeast 61 and in patients with methylmalonic aciduria and vitamin B12 impaired synthesis. 62 In the latter cases, mutated mitochondrial gene induces a signal to the nucleus, to activate mtDNA replication. 62 Previously, we proposed KSS as a neurocristopathy, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…62 In the latter cases, mutated mitochondrial gene induces a signal to the nucleus, to activate mtDNA replication. 62 Previously, we proposed KSS as a neurocristopathy, i.e. a disease correlated with NCC abnormality on the basis of facial abnormalities.…”
Section: Discussionmentioning
confidence: 99%